2021
DOI: 10.1111/mam.12276
|View full text |Cite
|
Sign up to set email alerts
|

Spatial predictors and species’ traits: evaluating what really matters for medium‐sized and large mammals in the Atlantic Forest, Brazil

Abstract: fragments. Finally, generalist species also occurred in landscapes with low edge density and number of patches, but were more prevalent in landscapes with higher human population density. 5. We stress the importance of maintaining large forest fragments, considering the effects of landscape configuration on conservation strategies, and reducing anthropogenic disturbances to ensure a greater persistence of mammal species in the Atlantic Forest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 82 publications
0
4
0
1
Order By: Relevance
“…Species more sensitive to habitat loss, including forest-dependent and large-sized ones, tend to be the first to disappear [97,98], such as the jaguar (Panthera onca), which is virtually extinct from our study landscapes. Although the large forest patches have the higher species richness, of the 13 patches smaller than 1000 ha, only 2 did not present any sensitive species, while at least one threatened species was recorded in 14 out of the 18 sampled patches.…”
Section: Discussionmentioning
confidence: 99%
“…Species more sensitive to habitat loss, including forest-dependent and large-sized ones, tend to be the first to disappear [97,98], such as the jaguar (Panthera onca), which is virtually extinct from our study landscapes. Although the large forest patches have the higher species richness, of the 13 patches smaller than 1000 ha, only 2 did not present any sensitive species, while at least one threatened species was recorded in 14 out of the 18 sampled patches.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed the data per field sampling period, calculating the number of records and richness per site and period analyzed (Table S2). To calculate the number of records, we considered only the species with more than six records in the two periods analyzed to avoid the uncertainty of detectability (Rios et al., 2022). We calculated richness, considering all wild species of medium and large‐sized mammals recorded.…”
Section: Methodsmentioning
confidence: 99%
“…A quarter of extant species are threatened and the risk of extinction has increased dramatically (Johnson et al., 2017; Turvey & Crees, 2019) in the last 40 years (Di Minin et al., 2016). However, recent studies have shown that many mammals differ in their level of sensitivity to anthropogenic (Haro‐Carrión et al., 2021; Rios et al., 2022) and seasonal changes (Cruz et al., 2018; Dias et al., 2019; Haro‐Carrión et al., 2021; Miles et al., 2006; Penido et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These data sets have provided an unprecedented opportunity for the assessment of how environmental conditions and species interactions can predict biodiversity patterns from species to assemblages (e.g. Bovendorp et al 2019, Palmeirim et al 2019, Rios et al 2021b, 2021a, Bonfim et al 2021. However, such studies rely on a highly variable set of spatial data and require intensive data processing, usually differing in the scale and grain, as well as source and quality.…”
Section: Introductionmentioning
confidence: 99%